Meminimalisir Bencana Kekeringan Menggunakan Sumur Resapan, Biopori, dan Parit Rorak di Desa Jembatan Kembar Timur, Kecamatan Lembar, Kabupaten Lombok Barat - Ali, Ahmad Muhammad; Waiduri, Siti Zuhara Faradisa; Saidah, Humairo; Hijriati, Awwalus Sanatil; Niam, Siti Nur Dian; Azizah, Fitri; Aulani, Haniatul; Putra, Rizki Pradana; Azizah, Hayatul; Qarina, Husnul; Khalil, Lutfhi Riza (Jurnal Gema Ngabdi, 2024)
Drought is a natural phenomenon in which people have limited access to water resources which are a vital requirement for human, animal, and plant. Drought has a significant impact on human life and is usually directly related to the arising of poverty, outbreaks of disease triggered by sanitation problems, crop failure, hunger, and death. Tibu Lilin Hamlet is one of the areas prone to drought. So, this activity aims to disseminate information on simple water-saving technology through infiltration wells, biopores and rorak ditches. The method used is through counseling and socialization. Socialization activities have been carried out and participated in by the community around the Nurul Jibal mosque. The public enthusiastically listened and actively discussed with the Team. This activity broadened the knowledge of the residents of Tibu Lilin Hamlet regarding the importance of groundwater storing through infiltration wells, biopores and rorak ditches.